[OP.8A.05] REGULAR PHYSICAL ACTIVITY ATTENUATES THE ASSOCIATION BETWEEN COFFEE CONSUMPTION AND CARDIOVASCULAR EVENTS IN HYPERTENSION. THE HARVEST. (September 2016) - Mos, L.; Fania, C.; Saladini, F.; Mazzer, A.; Cozzio, S.; Bortolazzi, A.; Garavelli, G.; Casiglia, E.; Palatini, P.
Abstract : Objective: Coffee consumption has been found to predict the risk of cardiovascular events (CVE) in hypertension. Aim of the present study was to ascertain whether the strength of the coffee-CVE association is modulated by regular physical activity. Design and method: The analysis was made in 1204 participants from the HARVEST, a prospective cohort study of non-diabetic subjects aged 18–45 years, screened for stage 1 hypertension. Among the participants, 26.2% were abstainers, 62.8% were moderate coffee drinkers (1–3 cups/day) and 10.0% were heavy coffee drinkers (>3 cups/day). For physical activity level, 61.1% were categorized as sedentary (class 0), 14.9% as mild exercisers (class 1), 14.9% as amateurs (class 2), and 9.1% as competitive athletes (class 3). Results: The frequency of coffee drinkers was higher among the sedentary (77.4%) than the active (67.9%) subjects (p < 0.001). During a 12.6 year follow-up 70 participants developed a CVE. The rate of CVE was higher among the coffee drinkers (7.1%) than the abstainers (2.2%, p = 0.001) and was higher in the sedentary (7.2%) than the active (3.6%) subjects (p = 0.01). In a 2x2 sub-table the coffee-related difference in CVE was significant among the sedentary (p = 0.006) but not the active subjects (p = 0.22) with a Mantel-Haenszel Chi-Square = 8.3 (p = 0.004). In a multivariable Cox analysis, including age, sex, parental CVE, smoking, alcohol use, total cholesterol, follow-up hypertension, and a coffee-physical activity interaction term, coffee consumption was a significant predictor of CVE in heavy coffee drinkers (Hazard ratio, 95%CI; 3.3, 1.2–8.9) and was a borderline predictor in moderate drinkers (HR, 95%CI; 2.0, 0.9–4.5). In addition, a borderline negative interaction was found between coffee consumption and physical activity habits on risk of CVE (p = 0.05). Conclusions: These data confirm that coffee use is associated with increased risk of CVE in young-to-middle age subjects with stage 1 hypertension. However, the effects of coffee on risk of CVE is modulated by the individual level of physical activity. Regular physical activity seems to counteract the long-term deleterious effect of caffeinated coffee on the cardiovascular system.